2012
DOI: 10.5644/ama2006-124.51
|View full text |Cite
|
Sign up to set email alerts
|

Care providers’ needs and perspectives on suffering and care in Bosnia and Herzegovina and Cambodia

Abstract: This exploratory study aimed to obtain insight into field-level care providers' views on suffering and healing as well as existing obstacles and needs related to providing care to their clients. This research provides a "snapshot" for a better understanding of existing care systems in two post-conflict settings. By identifying existing approaches to care and the needs of the care provider community, this research might be useful in guiding psychosocial assistance programming in post-conflict settings. Utilizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
2
1
Order By: Relevance
“… 7 Additionally, resettlement country studies have largely reported on health care provider populations which are culturally distinct from the refugee population. 18 In contrast, this study demonstrates that 28% of the medical trainees were themselves from the same countries as refugees, including Burundi, Democratic Republic of Congo, Somalia, and South Sudan. Educational needs around cultural competency may, therefore, be different in this setting.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“… 7 Additionally, resettlement country studies have largely reported on health care provider populations which are culturally distinct from the refugee population. 18 In contrast, this study demonstrates that 28% of the medical trainees were themselves from the same countries as refugees, including Burundi, Democratic Republic of Congo, Somalia, and South Sudan. Educational needs around cultural competency may, therefore, be different in this setting.…”
Section: Discussioncontrasting
confidence: 60%
“…To our knowledge, only one study in the field of trauma-informed care by McDonald and colleagues has reported on provider perspectives in host countries. 18 …”
Section: Introductionmentioning
confidence: 99%
“…Suffering may be attributed to physical or psychological distress, experienced or anticipated [ 4 ]. It may also be due to personal or social consequences of illness or disorders, or it may be embodied within social problems encountered in society, such as subjugation, violence, or poverty [ 2 , 6 ]. Suffering is highly subjective [ 7 ] and individual to each patient [ 8 ].…”
Section: Introductionmentioning
confidence: 99%